RENCANA PENGEMBANGAN KAWASAN MANGROVE NEGERI WAAI MENJADI OBJEK EKOWISATA BERBASIS MITIGASI BENCANA - Soplero, Excellion; Titaley, Stevianus; Papilaya, Renoldy Lamberthy (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2024)
Tourism is an important sector in boosting the economy and improving the welfare of the Indonesian people, including in coastal areas like Negeri Waai. With 4 hectares of mangroves, the ecotourism potential in this area is very promising, but it has not yet been optimally utilized for community welfare or disaster mitigation. This study aims to assess the condition of mangroves in Waai and plan the development of disaster-mitigation-based ecotourism. Using descriptive methods with both qualitative and quantitative approaches, data were collected through field surveys and literature reviews. The mangrove vulnerability index was calculated using the Coastal Vulnerability Index (CVI), while the suitability of the area for ecotourism was evaluated based on attractiveness, accessibility, and infrastructure. The study found 7 species of mangroves with a density of 2,068 stands per hectare, and the CVI indicated low vulnerability. According to ADO-ODTWA criteria, this area is highly suitable for ecotourism.